2016
DOI: 10.5604/01.3001.0009.3736
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of treatment of sinonasal inverted papillomas (IPs) depending on the surgical technique and learning curve.

Abstract: Endoscopic procedures are an effective method of IP treatment, however reasonable indications and surgeon experience should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The recurrence rate of SNIP after an open approach varies in different studies, depending on the follow-up period, completeness of resection, and malignancy. 14,15,16 However, a recent systematic review found a significantly higher recurrence rate associated with open approaches than endoscopic approaches (16.58% vs.12.8%, respectively). 17 Improvements in endoscopy technology have led to a growing preference for a less invasive endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rate of SNIP after an open approach varies in different studies, depending on the follow-up period, completeness of resection, and malignancy. 14,15,16 However, a recent systematic review found a significantly higher recurrence rate associated with open approaches than endoscopic approaches (16.58% vs.12.8%, respectively). 17 Improvements in endoscopy technology have led to a growing preference for a less invasive endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, it is shown to have lower recurrence rates. [14][15][16][17] However, it is important to note that the use of endoscopy and other surgical instruments by less experienced operators may lead to incomplete removal of tumors or potentially catastrophic complications, such as penetration into the orbit or intracranial. 16…”
Section: Discussionmentioning
confidence: 99%
“…First, SNIP is locally aggressive, often presenting with bony destruction and involvement of critical neurovascular structures 2 . Second, it has a high recurrence rate, estimated to be as high as 20% to 32% in some series 3,4 . Third, it shows a high propensity for malignant transformation and is associated with synchronous malignancy in 5% to 15% of cases and metachronous malignancy in 3% to 4% of cases 2,5 …”
mentioning
confidence: 99%
“…2 Second, it has a high recurrence rate, estimated to be as high as 20% to 32% in some series. 3,4 Third, it shows a high propensity for malignant transformation and is associated with synchronous malignancy in 5% to 15% of cases and metachronous malignancy in 3% to 4% of cases. 2,5 Because of these uniquely aggressive features, it is critical to properly diagnose and manage this pathology.…”
mentioning
confidence: 99%